Ghana: Processes and outputs associated with the UN Food Systems Summit - Asante, Felix A. (International Food Policy Research Institute, 2024)
Like other countries in the sub-region particularly West African economies, Ghana is grappling with multiple burdens of malnutrition which is accompanied by climate change that influence food production and consumption trends, and thereby leading to undernutrition and affecting overall development. In addition, growing incomes, accelerated urbanization, and expanding middle classes are also causing significant changes in consumer behavior and nutritional choices, necessitating both public and private expenditures for better food market integration. While food insecurity, and undernutrition (e.g. stunting, micronutrient deficiencies) persist, obesity and diet-related non-communicable diseases are rising rapidly. General nutrition situation and identification of the highest priority nutrition problems. Various estimates of nutritional status of Ghanaian children under aged 5 years show that 19% were stunted, 5% were wasted, and 11% were underweight. In 2018, the Multiple Indicator Cluster Survey (MICS) showed nearly similar rates of stunting (18%), wasting (7%) and underweight (13%), suggesting that stunting prevalence improved only marginally during the last 5-6 years, whereas child wasting and underweight worsened during the period. Other significant problems of undernutrition in Ghana include a high prevalence anemia in children 6-59 months (55%), adolescent girls (48%) and women of reproductive age (42%). From the foregoing, the high priority nutrition challenges in Ghana, include “stunting and wasting in children under 5 years of age; anemia in children 6-59 months of age, adolescent girls, and women of reproductive age; but also, overweight and obesity in school-age children and younger adolescents; and overweight and obesity in women of reproductive age (15-49 y of age). Report of the Demographic and Health Surveys show a significant rising trend in adult obesity – from 10% in 1993 to 40% in 2015 (GSS et al., 2015). Also, the Ghanaian food environments (particularly in the urban areas) is currently characterized by cheap highly-processed foods, with nutrient-dense foods such fruits and vegetables lacking in meals because it is unaffordable (Laar, 2021).